2021
DOI: 10.2147/jir.s332408
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Inflammation and Overall Survival in Elderly Patients with Cancer Cachexia – Results from a Multicenter Study

Abstract: Background: Systemic inflammation and cachexia are associated with adverse clinical outcomes in elderly patients with cancer. The survival outcomes of elderly patients with cancer cachexia (EPCC) with high inflammation and a high risk of mortality are unknown. This study aimed to investigate the impact of high inflammation on the prognosis of EPCC patients with high mortality. Patients and Methods: This multicenter cohort study included 746 EPCC (age >65 years) with a mean age of 72.00 ± 5.24 years, of whom 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Our multivariate survival analysis with different adjustment models showed that CRP, GNRI, ALI, and LCR all had significant survival predictive values in elderly patients with cancer. Similarly, previous studies have shown that CRP (11), GNRI (12), ALI (13), and LCR ( 14) can predict the prognosis of patients with cancer. Therefore, we developed and constructed SIPS, which consisted of CRP, GNRI, ALI, and LCR.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our multivariate survival analysis with different adjustment models showed that CRP, GNRI, ALI, and LCR all had significant survival predictive values in elderly patients with cancer. Similarly, previous studies have shown that CRP (11), GNRI (12), ALI (13), and LCR ( 14) can predict the prognosis of patients with cancer. Therefore, we developed and constructed SIPS, which consisted of CRP, GNRI, ALI, and LCR.…”
Section: Discussionsupporting
confidence: 59%
“…Blood samples were collected to measure serum markers, namely, CRP, neutrophils (N), lymphocytes (L), platelets (P), glucose (Glu), albumin (ALB), and globulin (GLB). These baseline inflammatory markers constituted the following ratios and indices: NLR (N/L ratio) ( 13 ), PLR (P/L ratio) ( 13 ), prognostic nutrition index (PNI), 10 × ALB + 0.005 × L) ( 13 ), systemic immune-inflammation index (SII), P × NLR) ( 13 ), ALI (BMI × ALB/NLR) ( 13 ), CAR (CRP/ALB ratio) ( 17 ), AGR (ALB/GLB ratio) ( 18 ), LCR (L/CRP ratio) ( 14 ), GNRI (1.489 × ALB + [Present body weight (PBW)/Ideal body weight (IBW)]) ( 12 ), mGNRI (modified GNRI, 1.489 × CRP + 41.7 × PBW/IBW) ( 12 ), and nutritional risk index (NRI), 1.519 × ALB + 41.7 × PBW/IBW) ( 19 ). IBW was evaluated using the Lorentz equation: men = height (cm) − 100 − [(height − 150)/4]; women = height (cm) − 100 − [(height − 150)/2.5] ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, more and more researchers focus on the relations between the immune-nutritional status and cancer ( 14 ). The controlling nutritional status (CONUT), as an immune-nutritional index deriving from peripheral blood variables of albumin (ALB), lymphocyte (LYM), and total cholesterol (TC), has been reported to be related to prognosis in various cancers, including ESCC ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%